ANALISIS PENGARUH CURRENT RATIO, RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN GROWTH TERHADAP RETURN SAHAM PADA COSMETICS AND HOUSEHOLD INDUSTRY YANG TERDAFTAR DI BEI PERIODE 2010-2016 - Tumonggor, Mutiara; Murni, Sri; Rate, Paulina Van (Universitas Sam Ratulangi, 2017)
Abstract: The high population that dominated by women make cosmetics become one of the important needs for women, so cosmetics companies become one of the target for investors. But not all companies can provide stock returns as expected. The purpose of this study was to determine the effect of Current Ratio (CR), Return On Equity (ROE), Debt to Equity Ratio (DER) and GrowthÂ on stock return. The method used in this research is quantitative method. The research population is 6 companies with purposive sampling technique taken 4 companies. The results shows customer CR, ROE, DER and growth has a significant effect on stock return. However, CR, ROE and DER does not have a significant effect on stock return. Based on these result, Cosmetics and household industry should improve the financial performance and consider the risks that may occur so as to increase the expected stock returns. Â Keywords: CR, ROE, DER, growth and stock return